LANDSCAPE APPROACH IN CITY-PLANNING - Boris I. Kochurov; Yulia A. Khaziakhmetova; Irina V. Ivashkina; Ekaterina A. Sukmanova (Юг России: экология, развитие, 2018)
Aim. The aim is to justify the application of the landscape approach in urban planning on the basis of theoretical concepts of landscape studies and the requirements of urban planning practices. Discussion. The basic scheme of the landscape approach is to study the natural and anthropogenic landscape as a complex geosystem consisting of a complex of various components which form the planning structure of the city. In territorial and urban planning, the structure and properties of natural and urban landscapes are revealed using functional, historical-genetic, morphotypic, geo-ecological and visual research methods. Abroad, a similar trend is called "landscape urbanism", the theoretical basis of which is based on the understanding that the best option for the organization of urban areas should be based on the landscape features of the city. With the use of the above-mentioned approaches, an urban landscape approach is being formed, a new nature-urban planning system which, in addition to natural complexes, includes man-made structures: buildings, infrastructure, parks and squares. If the natural landscape is a self-regulating geo-system, then the urban one is controlled by man. When taking actions to transform natural landscapes should be taken into account their structure and functioning, as well as the limits of possible impacts and the likely consequences of these changes. Conclusion. The demand for a landscape approach is constantly growing as a result of the significant transformation of modern cities, the replacement of architectural styles, the growth of urban space and communications, the desire to improve the quality of the urban environment and the comfort of the urban population.